On the Demise of the Social Discount Rate: Discussion - Herber, Bernard P. (Journal of Finance, 1971)
Bernard P. Herber, On the Demise of the Social Discount Rate: Discussion, The Journal of Finance, Vol. 26, No. 2, Papers and Proceedings of the Twenty-Ninth Annual Meeting of the American Finance Association Detroit, Michigan December 28-30, 1970 (May, 1971), pp. 581-583